P158 Intestinal Ultrasound at IBD diagnosis predicts surgery – a Copenhagen IBD cohort study. (30th January 2023) - Madsen, G R; Attauabi, M; Wilkens, R; Ilvemark, J F K F; Theede, K; Bjerrum, J T; Bendtsen, F; Seidelin, J B; Boysen, T; Burisch, J
Abstract: Background: The disease course of inflammatory bowel disease (IBD) is heterogeneous and unpredictable. Currently, we are unable to predict which patients will need IBD-related bowel resection in the first year after diagnosis. Intestinal Ultrasound (IUS) has been proven as a non-invasive modality for assessing disease activity in IBD. However, the evidence for IUS as a predictor of disease course is still limited. Here we present novel data on the predictive value of IUS performed at the time of IBD diagnosis. Methods: Patients with new-onset IBD are currently being included in the ongoing multicentre prospective inception cohort study, the IBD Prognosis Study (May 2021 – April 2023). IUS is performed at the time of diagnosis and the patients are followed prospectively. Patients with proctitis are not assessed with IUS. The International Bowel Ultrasound Segmental Activity Score (IBUS-SAS) is calculated for the most inflamed segment with a high score indicating severe disease activity. IBUS-SAS (0-100) incorporates the bowel wall thickness (BWT), bowel wall stratification, colour Doppler signal, and inflammatory fat. Surgery was defined as an IBD-related bowel resection. Patients treated with corticosteroids for > 72 hours or with any IBD-treatment > two weeks prior to IUS were excluded from analysis. In this abstract, we report our preliminary results after including patients for 16 months. Results: IBUS-SAS at diagnosis was available in 133 patients (out of 242 included). 68 patients were diagnosed with Crohn's disease (CD) (ilieal: 22, colonic: 23, ileocolonic: 23) and 65 patients were diagnosed with ulcerative colitis (UC) or unclassified IBD (left-sided colitis: 20, extensive colitis: 45). Median follow-up was 226 days. During follow-up 10 patients underwent surgery (7.5%). These included 4 patients with UC (extensive colitis: 3, left-sided colitis: 1) and 6 patients with CD (ileal: 2, colonic: 2, ileocolonic: 2). Mean IBUS-SAS at diagnosis was 92.6 among patients who underwent surgery during follow-up vs. 48.8 for patients who did not undergo surgery (p<0.0001). Distribution of scores is shown in Figure 1 . Mean BWT at diagnosis was 8.3 mm among patients who underwent surgery during follow-up vs. 5.0 mm for patients who did not undergo surgery (p<0.0001). In total, 12 patients had an IBUS-SAS > 90 at diagnosis and among these 7 (58.3%) were operated during follow-up. Figure 2 shows a Kaplan-Meier Curve of surgical free survival stratified by IBUS-SAS at diagnosis. Conclusion: IUS activity at diagnosis of IBD seems to have the capability to predict short term risk of IBD-related surgery. Our results suggest IUS might be used at diagnosis to identify patients at high risk of IBD-related surgery.